Legal Compliance and the Internalization of the Constitution: a Constitutional Rights Approach and Islamic Sociological Jurisprudence Theory in Strengthening the Rule of Law - Ahmad Muhammad Musta’in Nasoha; Maulida Ristia Ardhita; Meisya Putri Aulia; Safira Zahrotul Ulya; Tiara Luna Oktavia (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the relationship between legal compliance and the internalization of the constitution in strengthening the concept of the rule of law through a constitutional rights approach and the theory of Islamic Sociological Jurisprudence. The main issue addressed is the low level of legal compliance, which is often caused by a weak understanding and internalization of constitutional values in society. This research employs a normative juridical method with conceptual and sociological approaches, supported by an analysis of Islamic legal theory that emphasizes the interconnection between legal norms, social values, and morality. The findings indicate that legal compliance does not solely depend on formal law enforcement mechanisms, but also on the process of internalizing constitutional values as part of public legal awareness. The constitutional rights approach positions individuals as primary subjects who possess awareness of their rights and obligations, while the theory of Islamic Sociological Jurisprudence reinforces the moral and social dimensions in the formation of legal compliance. The integration of these two approaches can create a legal system that is not only normative in nature but also responsive to the social and religious values of society. Therefore, strengthening the rule of law requires a comprehensive strategy through legal education, the internalization of constitutional values, and the enhancement of moral awareness based on Islamic principles. This study is expected to contribute both theoretically and practically to the development of integrative and contextual legal studies in Indonesia.